Covariation of ionospheric influence in the GPS observations - Skeivalas, Jonas (Geodesy and Cartography, 2012)
The ionospheric influence on pseudo ranges and carrier phase observations is analysed in the paper. The state of the ionosphere is not constant and changes within the time as well as an ionospheric effect on GPS signals depend on their propagation geometry; therefore there is no constant error of coordinate determination due to the influence of the ionosphere. Theoretical values of correlation coefficient have been determined between two pseudo-ranges and between two carrier phase differences when signals are received from the same satellite at two different moments or from two different satellites at the same moment. It is demonstrated that attention should be paid to the correlation of observation results in GPS observations processing procedures. The ionospheric influence on point coordinates determination errors is analysed when coordinates are determined with a single-frequency GPS receiver in the absolute coordinate system.Article in Lithuanian.Jonosferos įtakos kovariacija atlikus GPS matavimusSantrauka. Straipsnyje analizuojama jonosferos įtaka atliekant pseudoatstumų ir nešlio fazių matavimus. Kadangi jonosferos būklė nėra pastovi, o kinta laike ir priklauso nuo GPS palydovų signalų sklidimo geometrijos, tai atitinkamai nėra pastovios matavimo taško koordinačių klaidos dėl jonosferos įtakos. Nustatytos koreliacijos tarp dviejų pseudoatstumų bei tarp dviejų nešlio fazių skirtumų, gautų priimant signalus iš to paties palydovo skirtingais laiko momentais arba iš skirtingų palydovų tais pačiais laiko momentais, koeficiento teorinės reikšmės. Parodyta, kad GPS matavimo rezultatų apdorojimo procedūrose turi būti atsižvelgiama į matavimo rezultatų koreliaciją. Analizuojama jonosferos įtaka taško koordinačių, nustatytų vieno dažnio GPS imtuvais, klaidoms absoliučiojoje koordinačių sistemoje.Prasminiai žodžiai: GPS, jonosfera, koreliacija, pseudoatstumai.First published online: 03 Aug 2012